The legal status of Jerusalem in the State of Israel (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction - 2. Background and Laws - 3. Legal Issues - 4. Future outlook.Abstract: Jerusalem is the most important city in the world, the Centre of the three greatest religions. It is the Capital of the State of Israel for some, the capital of the State of Palestine for others and for others still a corpus separatum under international control. Everyone wants Jerusalem, and so they contest it, creating political and legislative unrest. These disturbances give rise to violence from both groups of people that live there. In this brief dissertation, we retrace the key historical points and problems associated with the legal status of this city, from the first decades of the twentieth century, to understand that the problem lies in the claim of ownership of this City.
Keywords: Varie